PENGARUH PROMOSI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN MOTOR HONDA PADA PT. MITRA KRIDA PERKASA - Evyanto, Winda; Saputra, Asron (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2023)
This research is a study of the effect of promotions and price on PT Honda's motorcycle purchase decisions. Mitra Krida Perkasa Batam. In this study, the independent variable is Promotion and Price, while the independent variable is purchase decision. The data used in this study are primary data obtained from research studies. The researchers distributed questionnaires to 141 respondents, and quantitative causality was used as the research method. The hypothesis is proven by multiple regression analysis. The study was conducted in several phases viz. The first step is to familiarize yourself with the theories of literature and gather information about the chosen and studied topic. The second step is to gather basic information through a survey. The third step is to test the usefulness of the data through validity and reliability testing. Step four, exploratory hypothesis testing with multiple regression for partial and simultaneous testing of hypotheses. In the fifth step, it is investigated whether the independent variables of the dependent variable can reinforce each other's influence or are related to each other. The results of this study show that partly advertisement and price have a large positive and significant effect on the purchase decisions of Honda motorcycles in PT. Mitra Krida Perkasa Batam and at the same time discount and price variables together have a significant and very positive effect on PT Honda's motorcycle purchase decisions Mitra Krida Perkasa Batam